Polymeric tubes prepared from poly (vinyl alcohol) fiber templates - Çavuşoğlu, Jesmi. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
In this study, the fabrication of covalently crosslinked polymeric tubes by using poly(vinyl alcohol) (PVA) fiber templates has been demonstrated. The crosslinking on the surface of PVA fiber templates was achieved by two different methods. In the first method PVA surface hydroxyl groups were reacted with difunctional crosslinkers. Crosslinking took place with several dialdehydes and diisocyanates, respectively. The conditions were adjusted to allow the reaction to occur only on the surface and unreacted PVA inner core was removed from crosslinked fibers. Tubular structures which have adjustable shell thicknesses were succesfully fabricated by glutaraldehyde (GA) and 1,6-hexamethylene diisocyanate (HMDI) crosslinked PVA microfibers. Ultraviolet-visible spectroscopy was used to investigate load/release properties of these tubular hydrogels with changing shell thicknesses. Fluorescein dye molecules were used for imaging and the succesful absorption of dye molecules inside the shells was observed by optical microscopy. Furthermore, hydrophilicity differences were predicted between the outer and the inner shells. The feasibility of this method in fabrication of nanotubes was also investigated. In the second method PVA fibers were first reacted with acryloyl chloride and 3-trimethoxysilyl propylmethacrylate, respectively, to get double bond functionalized PVA fibers. These pendant double bonds were used to photopolymerize the surface of PVA with other mono and/or difunctional acrylate monomers. It was observed that during dissolution of the inner core, the shells were ruptured which may be due to a rigid network formation by photopolymerization. Therefore, it was found that the first crosslinking method is more suitable to prepare such hollow structures whose shells can be adjusted in terms of crosslinking and thickness. It was concluded that such materials may have potential applications in entrapment and release of several molecules.
Keywords: Polyvinyl alcohol.; Vinyl polymers.